Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.18538/lthe.v15.n1.302
|View full text |Cite
|
Sign up to set email alerts
|

Student-led seminars as an active learning strategy to enhance English as a foreign language procrastinating students’ achievement

Abstract: Research has demonstrated that high percentages of undergraduate college students self-report they engage in academic procrastination which has significant adverse effects on academic progress with relative consistency. The present study was designed to help English as a foreign language (EFL) procrastinators study on a regular basis, and also to extend the learning of the high achievers. To do so, seventy English as a Foreign Language students in the study were classified by level of procrastination based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…This meta‐analysis demonstrated that the seminar teaching method is an effective method for improving active learning ability, knowledge scores, skill scores, classroom atmosphere, student collaboration, and interaction between students and teachers. Al‐Amri 9 designed student‐led seminars to help procrastinators study EFL. This produced significantly higher exam scores.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This meta‐analysis demonstrated that the seminar teaching method is an effective method for improving active learning ability, knowledge scores, skill scores, classroom atmosphere, student collaboration, and interaction between students and teachers. Al‐Amri 9 designed student‐led seminars to help procrastinators study EFL. This produced significantly higher exam scores.…”
Section: Resultsmentioning
confidence: 99%
“…This approach was also successfully applied to different areas of education like biology, medical, engineering, English as a foreign language (EFL), information technology (IT), and design educations. [7][8][9][10][11][12] Peer review is another active learning approach, where the students are required to critically think and comment on the materials provided by their classmates. The question we would like to address is how the teachers can make use of these two approaches of "learning by teaching" and "peer review" to design an improved teaching method and provide better-quality learning process for students.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation